The effect of infant vitamin B12 supplementation on neurodevelopment: a follow-up of a randomised placebo-controlled trial in Nepal. Issue 1 (14th January 2023) - Ulak, Manjeswori; Kvestad, Ingrid; Chandyo, Ram Krishna; Ranjitkar, Suman; Hysing, Mari; Schwinger, Catherine; Shrestha, Merina; Basnet, Sudha; Shrestha, Laxman P.; Strand, Tor A.
Abstract: The most critical period for brain development is before a child's second birthday. Standardised tests measuring neurodevelopment are more reliable when administered after this period. Severe vitamin B12 deficiency affects brain development and function. In a randomised, double-blind, placebo-controlled trial in 600 Nepalese infants (6–11 months at enrolment), we found no effect of 2 µg vitamin B12 daily for a year on neurodevelopment. The primary objective of the current study was to measure the effect of the intervention on the Wechsler Preschool and Primary Scale of Intelligence (WPPSI-IV) full scale intelligence quotient (FSIQ). We measured the effect on the Bayley Scales of Infant and Toddler Development 3rd edition at age 30–35 months ( n 555). At age 42–47 months ( n 533), we used the WPPSI-IV and subtests from the Neuropsychological Assessment, 2nd edition (NEPSY-II). We also used the FSIQ to estimate subgroup specific effects. The mean (sd ) WPPSI-IV FSIQ in the vitamin B12 group was 84·4 (8·4) and 85·0 (8·6) in the placebo group (mean difference −0·5 (95 % CI -1·97, 0·94), P = 0·48). There were no effect of the vitamin B12 on any of the other neurodevelopmental outcomes and no beneficial effect in any of the subgroups. In conclusion, providing 2 µg of vitamin B12 for a year in infants at risk of vitamin B12 deficiency does not improve preschool cognitive function.